Teaching Skills of CRE Teachers and Student Interest at Unklab Senior High School - Kaeng, Angelie Theresia; Kasingku, Juwinner Dedy; Aseng, Andrew Christian; Siby, Robert R (Papanda Publisher, 2025)
This study explores the relationship between Christian Religious Education (CRE) teachers' teaching skills and students' interest in learning at UNKLAB Senior High School, Airmadidi. The purpose of the research is to assess how effectively teachers' teaching skills influence students' engagement and interest in learning Christian religious subjects. Using a quantitative, descriptive, and correlational approach, data was collected from 81 respondents across various 11th-grade classes and analyzed with SPSS statistical software. The study reveals that CRE teachers' teaching skills are categorized as very high, based on an average score of 4.02. This indicates that teachers excel in transferring knowledge, explaining Christian concepts clearly, supporting faith development, and encouraging active student participation. Students' interest in learning, with an average score of 3.92, is categorized as high. Analysis shows that students are notably interested in attending religious education classes and viewing learning as a means of personal development. Inferential statistics using bivariate Pearson correlation demonstrate a very strong positive correlation (r = 0.820) between teachers' teaching skills and students' interest in learning, with a significance value of p = 0.00. This suggests that higher teaching skills are associated with increased student interest in Christian religious education. The findings emphasize the critical role of effective teaching in enhancing student engagement. Recommendations for educators include maintaining high teaching standards and using varied methods to sustain student interest. For future research, examining different educational levels or focusing on specific aspects of teaching skills could provide further insights.